INDONESIAN TERRORISM PRISONERS’ TREATMENT: A CASE STUDY AT NUSAKAMBANGAN CLASS IIA CORRECTIONAL INSTITUTION - Kasmanto Rinaldi; Rio Tutrianto (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
Proper and effective rehabilitation patterns for terrorist criminals remain a critical concern in Indonesian correction institutions. A thorough knowledge of extremism and terrorism remains a barrier to rehabilitation. Despite the significant loss of life resulting from the actions of the perpetrators, they maintain a conviction that their deeds are genuine and aligned with the principles espoused by Islam. The culprits' strong adherence to the imam's authority poses challenges to their willingness to consider perspectives that originate from their external groups. The results of this study showed that the pattern of rehabilitation that has been done has not been done to the fullest extent. This was found by using a qualitative approach and the case study method on the Nusakambangan correction institutions Class IIA, where data is collected through field observations and in-depth interviews with some key informants. The religious comprehension of incarcerated terrorists is deeply extremist. This is attributable, among other things, to the jail's poor quality of human resources in the rehabilitation process, the jail's lack of funds and supplies, and the convicts' inactivity in responding to government programs.